Effect of Sago Waste as Local Feed Resource That Gives Cellulose Enzyme in Feed on Carcass and Organ Characteristics of Broiler Chickens - Zulkarnain, Deki; Zuprizal, Zuprizal; Wihandoyo, Wihandoyo; Supadmo, Supadmo (Faculty of Animal Science, Universitas Gadjah Mada, ISSTAP 2017, 2017)
This study aims to determine the effect of using sago waste as a local feed ingredient with cellulase enzyme addition to wards carcass and organs characteristics of broiler chickens. Broiler with chicken mix sex grouped in into five different treatment groups with 6 replications. Each replication consisted of 10 heads that were randomly distributed. The treatment used sago waste with cellulose enzyme addition of 0.75 g/kg of sago waste with usage level of 0.00%, 5.00%, 10.00%, 15.00% and 20.00% of total basal feed. The parameters observed were the characteristics of carcass and organ digestive or broiler chickens. Data were analyzed by Completely Randomized Design (CRD) with undirectional pattern. If there was a significant mean difference between treatments, then proceed with Duncan's New Multiple Rang Test (DMRT). The results showed that the addition of the sago waste with cellulose enzyme addition in feed gave a significant difference (P<0.05) to broiler characteristic (slaughter weight, abdominal fat weight and abdominal fat percentage), but not significantly different to the organs digestive of broiler. The research concluded that the effect of using sago waste with enzyme cellulose addition of 0.75 g/kg were able to improve broiler carcass characteristics and more effective at the use of 15% level in broiler ration by not affecting the internal organs of broiler chickens.